THE PRODUCTIVITY OF WOMEN LABOR ON COCOA PLANTATION IN BANYUWANGI DISTRICT - Evita Sholiha Hani (UNEJ e-Proceeding, 2012)
Labor is the most important production factor in the production process because he/she coordinating the other production factors. Fee received is used for daily needs. Therefore, the government requires all enterprises to pay employees above the Regency Minimum Pay (Indonesia:UMK). In general, the wages of women labor in the agricultural sector is under the UMK. The purposes of this study are to determine the level of the laborproductivity of women, to analyze factors associated with labor productivity of women in the cocoa plantations, and income contribution of women labor to income household. The research was conducted at PT. Perkebunan Nusantara XII (limited) of Kalisepanjang Banyuwangi. The research methods used are descriptive and analytic method. The research result showed that (1) Labor productivity of women is low, (2) factors related toproductivity are age, experience, skill, number of household members, and household income, and (3) the level of contributions women's labor income to household income is moderate. Suggestions are recommended to increase the productivity of women labor in order to their household welfare increase is labor payment of PT. Perkebunan Nusantara XII (limited) refer to government regulation, the government gave sanction to the company that hired under the UMK and the woman labor force continues to increase the skill of picking the cocoa.